The Effectiviness Of SSI-Inquiry Based Learning To Improve Students’ Critical Thinking Skills And Global Citizen Character - Setianingsih, Irma; Ismawati, Riva; Juliyanto, Eko (JURNAL PENDIDIKAN SAINS (JPS), 2025)
The development of science learning is something that needs to be considered to face problems that arise. Critical thinking skills and global citizen character need to be possessed to face problems that arise. Based on previous research, students' ability to think critically is still in the low category and students' knowledge about global citizenship is still lacking. This research aims to analyze the effectiveness of the SSI inquiry based learning model in improving students' critical thinking skills and global citizen character. This research is a quantitative research with a quasi-experimental type and a non-equivalent control group design. The sampling technique used was purposive sampling. A significant difference was shown based on the results of data analysis in the T test <0.001 for critical thinking skills and 0.04 for global citizen character. A significant increase in critical thinking skills and global citizen character based on the average pretest and posttest scores occurred in the experimental class. These results are supported by the average experimental class N-Gain test results which show a significant increase in critical thinking skills and global citizen character. The conclusion of this research is that the SSI inquiry model is effective in improving students' critical thinking skills and global citizen character.